The Role of Faith Based Organisation in the Electoral Process in Nigeria - Oyewale, Peter Oluwaseun (Polit Journal Scientific Journal of Politics, 2024)
One of the major determinants of any good democratic process of any country is the foundation in which electoral process is built upon. The electoral process in a democratic society serves as the cornerstone. The significance of the electoral process extends far beyond the mere act of casting votes. Religion groups have played a crucial role in Nigerian electoral process; the role of Faith-Based Organizations (FBOs) in the electoral process in Nigeria is multifaceted and holds significant implications for the nation's democratic landscape. The paper, therefore examine the role of religion groups in the electoral process of Nigeria and how Faith Based Organisations have assisted in shaping and re shaping the process. This paper will benefit extensively on the oral interview with the major stakeholders most especially religious groups, electoral officers and politicians.